Developing morally responsible citizens through religious education: case study of a Maronite school - Ghosn, Margaret (Journal of Religious Education, 2016)
The mission of every Catholic school is to infuse the gospel values of faith, justice and love into the daily life of the school community. One of the key ways that Catholic schools can live this mission is through religious education, which emphasises the dignity of all people and service to neighbour. This paper examines a Catholic College community's commitment to ushering in the kingdom of God by the implementation of social justice and community engagement through secondary students' religious education program. The paper presents the theoretical basis through Scripture and Catholic social teaching and how focus upon the kingdom of God is expressed. It outlines the College's shifts from the study of the religious education curriculum to an effective model of community engagement. The shifts are from a uni-dimensional model of service, through a wider focus on service, to a model of community engagement which leads to student-initiated contributions as people of the kingdom of God.